Evaluating the coexistence of Imperial Cormorant and Rock Shag through isotopic niches at different colonies in central Patagonia, Argentina - Gatto, Alejandro Javier (2021)
Following the competitive exclusion principle, two closely-related species living in sympatry can only coexist if ecological niche partitioning occurs. Throughout their distribution range, Imperial Cormorant (Leucocarbo atriceps) and Rock Shag (L. magellanicus) often breed in mixed-species colonies in Patagonia, Argentina. Isotopic niche assessment of both species was performed during two breeding seasons (2010/11 and 2011/12) in three different colonies were they breed syntopically. The three colonies, Isla Gran Robredo (45°07'54''S, 66°03'40''W), Isla Leones (45°03'28''S, 65°35'08''W), and Isla Viana (45°11'27''S, 63°23'50''W), are located within the 'Patagonia Austral Marine Park'. Whole blood samples were obtained simultaneously from breeding adults of both species during the early chick stage and used for stable isotope analysis. Isotopic niche was described by means of centroid analysis and Bayesian ellipse-based metrics. The isotopic niche overlap between species was in general small or insignificant, suggesting niche partitioning, and the isotopic niche width in the different colonies and seasons was significantly smaller in the Imperial Cormorant than in the Rock Shag. However, the isotopic niche of the Imperial Cormorant in Isla Viana during the second study season was totally included in the isotopic niche of the Rock Shag, suggesting an important niche overlap. Results showed evidence that niche partitioning processes in these cormorants is context dependent. However, further studies are needed including independent measures of prey availability and niche evaluation at additional colonies where these species breed alone and with other cormorant species, considering that the metacommunity framework predicts that the combination of species in metapopulation contexts could be sometimes achieved through pairs of species with similar resource utilization.